A comprehensive review on bioplastic production from microalgae. (2022) - Rajpoot, Aman Singh; Choudhary, Tushar; Chelladurai, H.; Nath Verma, Tikendra; Shende, Vikas
Graphical abstract: Abstract: The increased global demand for plastic materials is increasing the production and consumption of plastic materials around the world. It has resulted in severe plastic waste pollution, which has affected both marine and terrestrial life. Microplastics can cause several health hazards. Plastics take a long time to decompose, and plastic recycling, incineration, chemical treatments, and landfills are not the optimum solutions for reducing plastic pollution. These characteristics lead to the search for ways to produce alternate biodegradable plastics that can decompose faster than conventional synthetic plastics. Microalgae are abundant in our ecosystems and can be collected, processed, and utilised to make biopolymers easily. Microalgae have no harmful effects but have a faster growth rate and the capacity to cultivate in wastewater. The polysaccharides in the algae can be used to produce biodegradable plastic. This study investigates the economic viability and the ability of microalgae to produce biodegradable plastic. Hence, the two newly identified environmentally friendly approaches are discussed in this article: plastic biodegradation and bioplastic production using microalgae.